Radiographic alterations of the frontal sinus morphology according to variations of the vertical angle in posteroanterior radiographs of the skull (Acta Scientiarum. Health Sciences, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.20243The frontal sinuses play a highly relevant role in comparative human identification processes. Since forensic radiology is a branch in the forensic sciences, adequate radiological analysis of the frontal sinuses is essential for comparative human identifications. The current study investigates radiographic morphological changes in the frontal sinuses according to vertical angle distortions in posteroanterior (PA) radiographs. A standard PA radiograph of the skull of an adult was obtained. Eight addition PA radiographs were taken at different vertical angles. Frontal sinuses were analyzed qualitatively and quantitatively according to Ribeiro´s (2000) technique. Both qualitative and quantitative analyses revealed significant image distortions. Further, overlapping anatomical structures were reported when PA radiographs were analyzed in negative angulation distortions (from -10° to -40°). Positive and negative angular distortions up to 20º slightly affected the qualitative morphological analysis. However, 10° positive and negative distortions provided a significant interference in quantitative analysis and impaired the measuring process. Most forensic techniques for the analysis of frontal sinuses comprise measurements of morphological distances. Distortions of approximately 10° or over in vertical angulation of cranial PA radiographs should be avoided so that more accurate comparative human identifications could be achieved.